The Oxford Dictionary of music - Kennedy, Michael (Oxford, 2006)
The Oxford Dictionary of Music is an indispensable guide for all music lovers and performers, It brings together an unrivalled collection of entries covering musical subjects of all kinds in an authoritative and accessible way.